2012
DOI: 10.1080/14733145.2012.659747
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward seeking professional psychological help among Chinese students at a UK university

Abstract: Aim: In this study we aimed to investigate whether Chinese international and British home students at a university in the United Kingdom differed in their attitudes towards seeking psychological help. Method: The total sample comprised 323 participants. Participants completed measures to assess their attitudes toward seeking professional psychological help (recognition of need for psychological help, stigma tolerance, interpersonal openness, confidence in mental health practitioners). Results: Chinese students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Research with Chinese international students suggests that they are at great risk of developing mental health problems caused by cross‐cultural adjustment (Han, Han, Luo, Jacobs, & Jean‐Baptiste, ; Li, Liu, Wei, &, Lan, ). However, these students generally do not seek counseling, even if universities provide free counseling services (Tang, Reilly, & Dickson, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research with Chinese international students suggests that they are at great risk of developing mental health problems caused by cross‐cultural adjustment (Han, Han, Luo, Jacobs, & Jean‐Baptiste, ; Li, Liu, Wei, &, Lan, ). However, these students generally do not seek counseling, even if universities provide free counseling services (Tang, Reilly, & Dickson, ).…”
mentioning
confidence: 99%
“…Research with Chinese international students suggests that they are at great risk of developing mental health problems caused by cross-cultural adjustment (Han, Han, Luo, Jacobs, & Jean-Baptiste, 2013;Li, Liu, Wei, &, Lan, 2013). However, these students generally do not seek counseling, even if universities provide free counseling services (Tang, Reilly, & Dickson, 2012). The underutilization of mental health services by international students has been well documented (Austin, Carter, & Vaux, 1990;Khawaja & Stallman, 2011;Mori, 2000).…”
mentioning
confidence: 99%
“…McMahon identifies other factors as the importance of academic success, a lack of confidence in the English language and a reluctance to ask questions in class. In a study on attitudes to seeking professional help among Chinese students in the United Kingdom, Tang et al (2012) found that the students exhibited significantly less interpersonal openness than British students.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Much of the research on international college students has been conducted at academic institutions in the United States, and therefore, the experiences of international college students outside of the United States also warrant exploration. Tang, Reilly, and Dickson (2012) examined Chinese international students' experiences at a university in the United Kingdom. Specifically, the researchers measured a number of factors that influence help-seeking attitudes.…”
Section: Researchers Have Investigated Other Potential Barriers To Hementioning
confidence: 99%
“…British and Chinese international students did not differ in other mental health attitudes such as confidence in mental health practitioners, recognition for psychological help, and stigma tolerance (the ability to see counseling as a viable option despite social and self-stigma attached to it). These results may indicate that Chinese international students would be less likely to feel comfortable opening up to others about emotional difficulties which would make seeking help from mental health services unappealing (Tang, Reilly, & Dickson, 2012). To be emotionally open about one's struggles and seeking therapy may violate Asian cultural norms, as seeking mental health services is perceived as stigmatized in Asian cultures (e.g.…”
Section: Researchers Have Investigated Other Potential Barriers To Hementioning
confidence: 99%